2020
DOI: 10.2174/1570159x18666200507081531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulberry on The Central Nervous System: A Literature Review

Abstract: Background: Mulberry, including several species belonging to genus Morus, has been widely used as a traditional medicine for a long time. Extracts and active components of mulberry have many positive neurological and biological effects and can become potential candidates in the search for new drugs for neurological disorders. Objectives: We aimed to systematically review the medical literature for evidence of mulberry effects on the central nervous system. Methods: We conducted a systematic search in nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
(175 reference statements)
1
7
0
Order By: Relevance
“…Additionally, VEGF levels were rapidly upregulated after traumatic injury of the central nervous system 38 . Moreover, some research revealed that amber, cinnabaris, chrysanthemum, mulberry leaf might protect neuronal cells in the central nervous system 39–42 . Therefore, we speculated that HPASD equally with a protective effect on the nervous system.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, VEGF levels were rapidly upregulated after traumatic injury of the central nervous system 38 . Moreover, some research revealed that amber, cinnabaris, chrysanthemum, mulberry leaf might protect neuronal cells in the central nervous system 39–42 . Therefore, we speculated that HPASD equally with a protective effect on the nervous system.…”
Section: Discussionmentioning
confidence: 94%
“…38 Moreover, some research revealed that amber, cinnabaris, chrysanthemum, mulberry leaf might protect neuronal cells in the central nervous system. [39][40][41][42] Therefore, we speculated that HPASD equally with a protective effect on the nervous system. However, there is no specific mechanism for fracture repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, Morus alba called mulberry has been evaluated as a safe herb showing no side effects [16,17]. The fruits, leaves, branches, and roots of mulberry possess a range of biological treatment effects on numerous human diseases [18,19], including diabetes, neurological disorders, cardiovascular diseases, and cancers [20][21][22][23][24]. However, there has not been sufficient research proving that mulberry can function as a therapeutic agent in oral diseases and its related oral risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…At present, mulberry leaf tea has been developed in various forms as a functional food in the prevention and treatment of diabetes in China [19][20][21]. Modern studies have proved that mulberry leaves are rich in alkaloids, flavonoids, polysaccharides and other functional components, which can reduce blood sugar, blood pressure, blood lipids, antiaging, anti-oxidation and anti-nervous system diseases [22][23][24][25]. Recently, "total alkaloids from Ramulus Mori", the first new approved TCM for diabetes in the past 10 years in China, was put on the market.…”
Section: Introductionmentioning
confidence: 99%